Value-Added Tax apportionment methodology applied in the higher sector of South Africa : Is the apportionment method currently applied in the higher education sector effective and appropriate in a South African context? - Nelson, Ludwig W (Department of Finance and Tax, 2016)
This dissertation focusses on the value-added tax apportionment methodology applied in the higher education sector of South Africa. The current apportionment method applied by universities is the varied input-based method. The research question that is posed, is whether the varied input-based method is effective and appropriate in the higher education sector in a South African context and whether or not there are other solutions which could apply to alleviate the burden that apportionment has placed on the universities. In addressing the research question the dissertation specifically discusses the principles of apportionment, turnover-based method, input-based method and varied input-based method. Furthermore, the dynamics of the higher education sector is discussed in detail with specific focus on the income streams and expense types of universities and how this influences the application of apportionment methods. Lastly, other solutions are considered such as a reduced Value-Added Tax rate for the supply of educational services and the zero-rating of the supply of educational services. It is concluded that the varied input-based method is definitely not the long term solution as the difficulty in its application and the financial burden makes it impracticable to use. Also, it is concluded that a possible solution is to zero-rate the supply of educational services by universities in terms of section 11 of the Value-Added Tax Act No. 89 of 1991. This would not only alleviate the burden of apportionment, but also result in universities being allowed to claim all the VAT it incurs (except for input tax denied in terms of section 17(2) of the Value- Added Tax Act No. 89 of 1991) and result in a net gain for the universities. Whatever is decided, the current investigation of apportionment methodology applied in the higher education sector of South Africa needs to be concluded as soon as possible and a clear practical and sustainable approach needs to be agreed upon, as it is in the best interest of all of the parties involved as well as South Africa and the education of its people as a whole.